“Selling Blood, Reading Pain”: Indonesian Readers' Responses to Sacrifice and Black Humor in Yu Hua's Chronicle of a Blood Merchant - Elizabeth Irene Hartanto (Mandarinable: Journal of Chinese Studies, 2026)
This study examines Indonesian readers' responses to sacrifice and black humor in Yu Hua's Chronicle of a Blood Merchant. The novel tells the story of Xu Sanguan, a poor peasant who sells his blood repeatedly to support his family. What makes this novel distinctive is its unique narrative tone: a blend of tragedy and dark humor, using qualitative thematic analysis of 35 reader reviews from Goodreads and online book blogs, this research focuses on two aspects: how Indonesian readers respond to Xu Sanguan's sacrifices; and how they experience the novel's black humor. The findings reveal three key patterns. First, Indonesian readers strongly empathize with Xu Sanguan's sacrifices, appreciating his transformation from a selfish young man to a devoted father. Second, readers consistently recognize and appreciate the novel's black humor, describing their experience as "laughing and crying at the same time," what critics call "humor under the gallows". Third, the combination of sacrifice and dark humor makes the novel's critique of China's revolutionary era more accessible to Indonesian readers, who understand the universal themes of suffering, resilience, and family love. This study contributes to the cross-cultural reception of contemporary Chinese literature in Indonesia and offers insights into how Indonesian readers navigate themes of sacrifice, resilience, and laughter across cultural boundaries.